Penataan Stasiun Kerja Industri Pelapisan Logam UD. Langgan Abadi Berdasarkan Prinsip 5R untuk Efisiensi Proses Kerja - wahyuni, ida (2020, 2020)
One of the informal sector businesses that absorbs a lot of labor is electroplating or metal plating services. This sector has a high risk of accidents and illness due to a combination of labor and environmental factors. Epidemiological studies show that workers exposed to chromate production and Cr coating have 2-80 times the risk of lung cancer. That work places requires optimization of work station layout. The purpose of rearranging work station layout based on the 5S principle to improve the productivity and work efficiency in the metal coating industry UD. Langgan abadi. This activity used an observation and two way communication method that begun with a pretest and ended with a posttest. Participants in this activity were business owners and metal coating workers in Talang sub-district, Tegal district. After rearranging, the work station becomes neat, has adequate lighting and ventilation and also the work posture becomes ergonomic. Rearranging work stations based on the 5S principle can improve work efficiency and effectiveness which increases productivity. Keywords— Work Station, 5S, efficiency, productivity